Las canteras subterráneas y el urbanismo (la STSJPV de 3 de diciembre de 2014) - Javier Moreno García (Revista Vasca de Administración Pública, 2016)
This chronicle gives account of the judgment delivered by the High Court of the Basque Country cancelling a municipal licence that denied the permit for an underground quarry.The judgment is of great interest for the three-dimensional spatial planning in a dual sense: on the one hand, it endorses the correct conception for stratified territory with diverse uses depending on the height; on the other hand, nevertheless, it puts a brake to the equal treatment in surface and subsurface uses which I consider not reflected by the legal order and that runs counter to a correct land use in particular when it points out that extractive underground activities are not subject to the duty of being demarcated by urban planning as it is the case of those opencast, just as it is prescribed by the binding determinations of the Regional planning guidelines. Besides, it allows the subsurface extractive underground use although the planning shall not affect that space for the aforementioned purpose.